Emergence of high-level colistin resistance mediated by multiple determinants, including mcr-1.1, mcr-8.2 and crrB mutations, combined with tigecycline resistance in an ST656 Klebsiella pneumoniae - Wang, Yanfei; Zhou, Junxin; Liu, Haiyang; Wang, Qian; Zhang, Ping; Zhu, Jingyi; Zhao, Dongdong; Wu, Xueqing; Yu, Yunsong; Jiang, Yan (Frontiers in Cellular and Infection Microbiology, 2023)
Colistin and tigecycline are usually regarded as the last resort for multidrug-resistant Klebsiella pneumoniae infection treatment. Emergence of colistin and tigecycline resistance poses a global healthcare challenge and is associated with high mortality due to limited therapeutic options. Here, we report the ST656 extensively drug-resistant K. pneumoniae strain KP15-652, which was isolated from a patient’s urine in China. Antimicrobial susceptibility testing showed it to be resistant to tigecycline, amikacin, levofloxacin, ciprofloxacin, and high-level colistin resistance (> 2048 mg/L). Whole-genome sequencing revealed that it harbors one chromosome and seven plasmids, including four plasmids carrying multiple acquired resistance genes. Transformation/conjugation tests and plasmid curing assays confirmed that mcr-1.1, mcr-8.2 and crrB mutations are responsible for the high-level colistin resistance and that a series of efflux pump genes, such as tmexCD1-toprJ1, tet(A) and tet(M), contribute to tigecycline resistance. mcr-1.1 and tet(M) are located on an IncX1 plasmid, which has conjugation transfer potential. mcr-8.2 and tet(A) are located on a multireplicon IncR/IncN plasmid but unable to be transferred via conjugation. Moreover, another conjugable and fusion plasmid carries the tmexCD1-toprJ1 gene cluster, which may have arisen due to IS26-mediated replicative transposition based on 8-bp target-site duplications. Importantly, a complex class 1 integron carrying various resistance genes was detected on this fusion plasmid. In conclusion, it is possible that the high-level of colistin resistance is caused by the accumulated effect of several factors on the chromosome and mcr-carrying plasmids, combined with many other resistances, including tigecycline. Effective surveillance should be performed to prevent further dissemination.